Combining and managing work-family-study roles and perceptions of institutional support. Issue 1 (2nd January 2021) - Samra, Rajvinder; Waterhouse, Philippa; Lucassen, Mathijs
ABSTRACT: Students registering for distance education degree-level study frequently cite flexibility as a factor influencing their choice for this mode of study, but little is known about how students manage simultaneous and/or potentially conflicting roles. This study used a self-report open-ended online survey, completed by 348 tertiary-level final-year undergraduate distance students in the United Kingdom. Respondents were asked how they managed to combine roles and their perceptions of university support. After a thematic analysis, three main themes were identified: building rituals and habits for learning, navigating online environments and contexts for learning, and responding to the pressures and problems that hindered their learning. Students expressed a desire for more proactive support from tutors. From the university, students wanted realistic and practical guidance and planning tools to prepare themselves and others (such as their employers and family) for the likely practical requirements of distance study when combining multiple roles.